TEAD transcription factor family emerges as a promising therapeutic target for oral squamous cell carcinoma - Wang, Shuang; Shao, Dan; Gao, Xiaoyan; Zhao, Peng; Kong, Fanzhi; Deng, Jiawei; Yang, Lianzhu; Shang, Wei; Sun, Yaping; Fu, Zhiguang (Frontiers in Immunology, 2024)
The treatment of oral squamous cell carcinoma (OSCC) remains a significant difficulty, as there has been no improvement in survival rates over the past fifty years. Hence, exploration and confirmation of new dependable treatment targets and biomarkers is imperative for OSCC therapy. TEAD transcription factors are crucial for integrating and coordinating multiple signaling pathways that are essential for embryonic development, organ formation, and tissue homeostasis. In addition, by attaching to coactivators, TEAD modifies the expression of genes such as Cyr61, Myc, and connective tissue growth factor, hence facilitating tumor progression. Therefore, TEAD is regarded as an effective predictive biomarker due to its significant connection with clinical parameters in several malignant tumors, including OSCC. The efficacy of existing drugs that specifically target TEAD has demonstrated encouraging outcomes, indicating its potential as an optimal target for OSCC treatment. This review provides an overview of current targeted therapy strategies for OSCC by highlighting the transcription mechanism and involvement of TEAD in oncogenic signaling pathways. Finally, the feasibility of utilizing TEAD as an innovative approach to address OSCC and its potential clinical applications were analyzed and discussed.